(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The following article reflects the views of Uzbek linguist A. Gulomov, who made a great contribution to Uzbek linguistics sciences. In his scientific works, the scientist pays great attention to the analysis of additives. The period of creation of serious scientific research on the morphology of the Uzbek language falls on the 40’s of the XX century - the years created by A. Gulomov.